Aplikasi Asam Giberelin dan Peletakan Akar Terhadap Produksi Benih Padi (Oryza sativa L.) Varietas Situ Bagendit - Yudha, Yanuar Satya; Rahmawati, Dwi (Agropross : National Conference Proceedings of Agriculture, 2023)
Rice is one of the main food sources for the people of Indonesia, therefore it is necessary to increase rice production to meet these needs. The purpose of this study was to determine the interaction of Gibberellin application and horizontal root placement on rice seed production. This research was conducted in Triwungan Village, Kota Anyar Subdistrict, Probolinggo Regency from August to November 2022. The implementation of the research used a Randomized Group Design (RGD) which was repeated 4 times. The first factor is GA3 concentration which consists of 4 levels, namely G0 (0 ppm), G1 (200 ppm), G2 (250 ppm), G3 (300 ppm). The second factor is the placement of root position consisting of A1 (vertical placement), A2 (horizontal placement). Observational data were analyzed using ANOVA, if there was a significant difference between treatments, it was continued with LSD further test at 1% level. The results showed that horizontal root laying showed a result of 2.35 in the number of tillers 4 weeks after planting. Gibberellin concentration of 250 ppm with the results of 20.625 cm on the parameters of panicle length, 70.04 grains on the number of grains per panicle, 57.21 grains on the number of grains per panicle, 25.99 grams on the weight of 1000